Assessment of biliary bicarbonate secretion in humans by positron emission tomography - Prieto, J; García, N; Martí-Climent, J M; Peñuelas, I; Richter, J A; Medina, J F (Gastroenterology (New York, N.Y. 1943), 1999)
Positron emission tomography (PET) allows imaging and quantitative analysis of organ functions in basal and stimulated conditions. We have applied this method to the study of biliary bicarbonate secretion in humans. PET was performed in 5 healthy subjects and 13 patients with hepatobiliary disorders after intravenous injection of NaH11CO3. In each case the study was performed in basal conditions and after secretin stimulation. Positron emission from the hepatic area was scanned, and normalized uptake values for parenchymal and hilar regions were estimated. In healthy individuals, the injection of NaH11CO3 resulted in a peak uptake of the label in parenchymal and hilar regions 2-3 minutes after the injection. In both normal and cirrhotic subjects, secretin administration increased bicarbonate uptake in the parenchymal region, followed by accumulation of the label in the perihilar area. Normal basal uptake with absent response to secretin was registered in extrahepatic biliary obstruction and in untreated primary biliary cirrhosis (PBC). The secretin response was present in patients with PBC undergoing treatment with ursodeoxycholic acid. PET allows investigation of biliary bicarbonate secretion in humans. An impaired response to secretin was observed in cholestatic conditions. Preliminary data suggest that ursodeoxycholic acid might improve the response to secretin in PBC.